MASYARAKAT PULAU DI UTARA JAWA DAN PASANG SURUT BUDAYANYA - Koestoro, Lucas Partanda (BRIN, 1995)
Entering the twentieth century, there was a discussion on the nautical aspects of Indonesian culture. JC van Leur started to discuss the maritime nations in the